Admission high-sensitivity troponin T and NT-proBNP for outcome prediction in acute heart failure. (15th October 2019) - Aimo, Alberto; Januzzi, James L.; Mueller, Christian; Mirò, Oscar; Pascual Figal, Domingo A.; Jacob, Javier; Herrero-Puente, Pablo; Llorens, Pere; Wussler, Desiree; Kozhuharov, Nikola; Sabti, Zaid; Breidthardt, Tobias; et al.
Abstract: Background: High-sensitivity troponin T (hs-TnT) reflects the severity of ongoing myocardial damage. In acute heart failure (AHF), its additive prognostic value over B-type natriuretic peptides is unclear. Methods: Individual data of 1499 AHF patients with admission hs-TnT were collected from 3 cohorts. Results: Patients (78 ± 10 years, 51% men, N-terminal fragment of pro-B-type natriuretic peptide – NT-proBNP - 5660 [2693–12, 466], hs-TnT 43 ng/L [26–69]) experiencing in-hospital death ( n = 187, 13%) had significantly higher hs-TnT and NT-proBNP on admission (both p < 0.001). Patients with hs-TnT ≥43 ng/L and NT-proBNP ≥5660 ng/L had a 2.7-fold higher risk of in-hospital death (relative risk - RR 2.7, 95% confidence interval - CI 1.7–4.5). Among discharged patients, 1024 deaths (81%) occurred over 11 months (4–22). In the whole population, hs-TnT ≥43 ng/L predicted all-cause death at 6, 12 and 24 months independently from NT-proBNP ≥5660 ng/L. The best NT-proBNP cut-off for in-hospital mortality (4382 ng/L) independently predicted this endpoint, while the best hs-TnT cut-off (55 ng/L) did not. Patients with NT-proBNP ≥4382 ng/L and hs-TnT ≥55 ng/L had a 12-fold higher risk of in-hospital death (RR 11.7, 95% CI 6.9–19.7). The best hs-TnT cut-offs independently predicted all post-discharge outcomes. Conclusions: The best NT-proBNP cut-off (4382 ng/L) independently predicts outcome, while the best hs-TnT (55 ng/L) does not; patients with both biomarkers ≥best cut-offs have a 12-fold higher risk of in-hospital mortality. Admission hs-TnT ≥43 ng/L and the best hs-TnT cut-offs hold independent prognostic significance for post-discharge outcome, while hs-TnT seems less predictive than NT-proBNP when considering absolute values. Highlights: Admission hs-TnT 43 ng/L cut-off refines risk stratification of post-discharge outcome over NT-proBNP 5660 ng/L. Patients with NT-proBNP ≥4382 ng/L and hs-TnT ≥55 ng/L have an almost 12-fold higher risk of in-hospital death. hs-TnT ≥43 ng/L independently predicts post-discharge outcome over NT-proBNP ≥5660 ng/L. The best hs-TnT cut-offs are more predictive of post-discharge outcome than the best NT-proBNP cut-offs. Absolute NT-proBNP levels are more predictive than hs-TnT for post-discharge outcome.